1993
DOI: 10.1163/156856293x00230
|View full text |Cite
|
Sign up to set email alerts
|

Protein adsorption studies on 'standard' polymeric materials

Abstract: Adsorption of fibrinogen from buffer as a single protein and from plasma to four materials has been studied. The two NIH-NHLBI primary reference standards, filler free polydimethylsiloxane and low density polyethylene, were used along with polyvinylcholoride and cellulose materials supplied by the IUPAC Working Party. The materials were examined in both film and tubing form, except for polydimethylsiloxane which was studied only in tubing form. Adsorption was measured at room temperature using 125I-labelled fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…The surface energy of a substrate can affect the types and amounts of proteins that are able to adhere to the surface, affecting cell adhesion and behavior [40], [41]. We used water contact angle measurements to determine whether the surface energy was constant for the different PDMS formulations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The surface energy of a substrate can affect the types and amounts of proteins that are able to adhere to the surface, affecting cell adhesion and behavior [40], [41]. We used water contact angle measurements to determine whether the surface energy was constant for the different PDMS formulations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, as cellulose is a hydrophilic material with low nonspecific protein adsorption (which is why mammalian cells do not readily adsorb to cellulose surfaces) (Wu et al 2003;Zou et al 2001;Pelton 2009;Brash and Ten Hove 1993), these scaffolds required the addition of matrix ligands, to facilitate cell attachment to their surfaces (Singh et al 2013;Modulevsky et al 2014;Torres-Rendon et al 2015;Feldmann et al 2015). Watanabe et al (1993) demonstrated that, by introducing an ionic charge to cellulose membranes, collagen could be adsorbed to the membrane surface to promote cellular adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Guemouri et al [58] also demonstrated that the adsorption of extracellular matrix protein fibronectin on a Si 0.78 Ti 0.22 O 2 surface is a reversible process. The Langmuir isotherm, which has often been successfully applied to describe the adsorption of proteins onto solid surfaces [59][60][61][62], can be described by:…”
Section: Thus the Term [Q Amentioning
confidence: 99%